2011
DOI: 10.1161/atvbaha.110.216341
|View full text |Cite
|
Sign up to set email alerts
|

RhoJ/TCL Regulates Endothelial Motility and Tube Formation and Modulates Actomyosin Contractility and Focal Adhesion Numbers

Abstract: Objective-RhoJ/TCL was identified by our group as an endothelial-expressed Rho GTPase. The aim of this study was to determine its tissue distribution, subcellular localization, and function in endothelial migration and tube formation. Methods and Results-Using in situ hybridization, RhoJ was localized to endothelial cells in a set of normal and cancerous tissues and in the vasculature of mouse embryos; endogenous RhoJ was localized to focal adhesions by immunofluorescence. The proangiogenic factor vascular end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(109 citation statements)
references
References 32 publications
8
101
0
Order By: Relevance
“…Like the related formins FMNL1 and FMNL2 [4,5], FMNL3 interacted with activated Cdc42 ( Figure 1A) but also with RhoJ, RhoD, RhoH, and Rnd1. We focused on Cdc42 and RhoJ, as both signaling proteins are required for angiogenesis [6][7][8]. We confirmed the interactions with FMNL3 by co-immunoprecipitation in HEK293 cells.…”
Section: Fmnl3 Signals Downstream Of Cdc42 and Rhojmentioning
confidence: 68%
See 1 more Smart Citation
“…Like the related formins FMNL1 and FMNL2 [4,5], FMNL3 interacted with activated Cdc42 ( Figure 1A) but also with RhoJ, RhoD, RhoH, and Rnd1. We focused on Cdc42 and RhoJ, as both signaling proteins are required for angiogenesis [6][7][8]. We confirmed the interactions with FMNL3 by co-immunoprecipitation in HEK293 cells.…”
Section: Fmnl3 Signals Downstream Of Cdc42 and Rhojmentioning
confidence: 68%
“…Next, we sought to link FMNL3 to known endothelial functions of Cdc42 and RhoJ. RhoJ controls focal adhesion disassembly in endothelial cells (ECs) through regulation of the GIT-PIX complex [7,9]. We silenced FMNL3 in primary ECs (Figure S1B); however, this had no effect on focal adhesion number (data not shown), suggesting that FMNL3 is not involved in this aspect of RhoJ signaling.…”
Section: Fmnl3 Signals Downstream Of Cdc42 and Rhojmentioning
confidence: 99%
“…This model was based on one previously used with vascular endothelial cells (VEC) in the study of angiogenesis [36][37][38], and we report the first description of formation of comparable stable networks for LEC. Addition of platelets to these networks or crosslinking of podoplanin caused their disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Having shown that platelets and podoplanin crosslinking modulate VEGF-mediated LEC migration, we also examined their effects on networks of LEC, adapting a method described for vascular endothelial cells [36][37][38] but not yet reported for LECs. We found for the first time that stable networks of LEC could be established on monolayers of fibroblasts.…”
Section: Effects Of Platelets and Podoplanin Crosslinking On Stabilitmentioning
confidence: 99%
“…We explored the role of RhoJ in endothelial migration and tubulogenesis, and its regulation of the actin cytoskeleton, and mapped its subcellular localization and tissue distribution [14]. There have subsequently been two further reports noting an endothelial expression pattern and characterizing a role for RhoJ in endothelial cell biology [15,16].…”
Section: Endothelial Cells and Angiogenesismentioning
confidence: 99%